Blue lupine seed treatment effectiveness against lupine weevils’ imago - Shako, E. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The article presents research results, which were carried out in 2016—2017 to determine the blue lupine seed treatment effectiveness against lupine weevils’ imago. Seeds were treated with by insecticide Gaucho 70 WS (imidacloprid, 700 g/kg) with different concentrations. During the sampling, was found that average damage score of lupine vegetative weight on control variant was 2.5 and 2.2 in 2016 and 2017, respectively. With Gaucho 70 WS 2.5 kg/t, lupine had the lowest damage score — 0.8 and 0.5, and LSD0.05 — 0.29 and 0.55 confirms a significant difference between researching data and control variant. Technical efficiency against lupine weevils in this variant was 68.9% and 79.3%. It was specified abiotic factors influence during research years on the lupine weevils’ phenology.